2000
DOI: 10.1076/0271-3683(200008)2121-vft662
|View full text |Cite
|
Sign up to set email alerts
|

Expression of membrane-type 1 matrix metalloproteinase (MT1-MMP) and MMP-2 in normal and keratoconus corneas

Abstract: The observation that MT1-MMP expression may be up-regulated in keratoconus corneas, taken together with the demonstration that human corneal cells can express this enzyme, which in turn can activate latent MMP-2, provide evidence for a possible role for MT1-MMP in the pathogenesis of keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 0 publications
3
38
0
2
Order By: Relevance
“…41,42 Incubation with the plant lectin con-A led to the activation of MMP-2 in tree shrew skin cells as has been reported for other fibroblast cells, including human corneal, dermal, and gingival fibroblasts. [42][43][44] This activation occurred at similar con-A concentrations to those reported for corneal fibroblasts. 44 The activation mechanism of con-A is thought to be via the MT1-MMP-mediated pathway.…”
supporting
confidence: 48%
“…41,42 Incubation with the plant lectin con-A led to the activation of MMP-2 in tree shrew skin cells as has been reported for other fibroblast cells, including human corneal, dermal, and gingival fibroblasts. [42][43][44] This activation occurred at similar con-A concentrations to those reported for corneal fibroblasts. 44 The activation mechanism of con-A is thought to be via the MT1-MMP-mediated pathway.…”
supporting
confidence: 48%
“…49 This is supported by the nonuniform proteoglycan distribution within the stroma. 50 The production of abnormal substances within the keratoconic stroma previously has been reported: with abnormal production of matrix metalloproteinase-2; 51 upregulation of the expression of MT1-MMP; 52 overexpression of keratocan; 53 reduction in expression of type X11 collagen 54 and modification of type V1 collagen synthesis 55 all being documented. Although keratocytes appear to provide a vital role in the stability of the corneal structure, 17 perhaps the corneal changes exhibited by keratoconics are due to substances synthesised or expressed by keratocytes.…”
Section: 39mentioning
confidence: 99%
“…In another study, keratoconic immunolabelling for MMP-1, -2 and -3 resembled that of the normal cornea and post LASIK keratectasia 61 while peroxidase immunohistochemistry performed by Collier's group showed that MMP-14 was significantly elevated in the keratoconic stroma 55 .…”
Section: Stromamentioning
confidence: 99%
“…Collier et al performed peroxidase immunohistochemistry and determined that MMP-14 (MT1-MMP) was significantly elevated in the epithelium of keratoconic corneas compared to eye bank controls, while MMP-2 was not 55 . This was surprising given that MMP-14 was previously shown to activate latent MMP-2 as well as being able to degrade matrix molecules directly.…”
Section: Epithelium and Increased Mmp-1mentioning
confidence: 99%
See 1 more Smart Citation